Enhancement of the cleavage rates of DNA-armed hammerhead ribozymes by various divalent metal ions. - Sawata, S (1993)
In order to characterize structure-function relationships, the kinetic behavior of chimeric RNA/DNA ribozyme was compared with that of all RNA ribozyme. Determined kcat values were proven to represent the chemical-cleavage step and not the product-dissociation step. In agreement with the finding by Dahm and Uhlenbeck [Biochemistry 30, 9464-9469 (1991)], various metal ions, including Co2+ and Ca2+ with the ionic radius of 0.65 and 1.0 A, respectively, could support hammerhead cleavage for both types of ribozyme. Measurements of kinetic parameters in the presence of various divalent metal ions revealed that DNA arms always enhanced kcat values. Chemical-probing data using dimethylsulfate indicated that the catalytic-loop structures of all-RNA and chimeric ribozymes were nearly identical with the exception of enhanced termination of primer extension reactions at C3 in the case of the chimeric ribozyme. These observations and others demonstrate that DNA substitution in non-catalytic-loop regions increases chemical-cleavage activity, possibly with an accompanying very subtle change in the structure.